Complete Mitogenome sequencing of the fish louse Argulus japonicus (Crustacea: Branchiura): Comparative analyses and phylogenetic implications - Wang, Lidan; Hu, Zun; Wang, Zhao; Zhu, Pengchen; Wei, Guoshan; Fan, Xinyi; Huang, Jiali; Wang, Ruixi; Wang, Hui; Xie, Yue (Frontiers in Veterinary Science, 2024)
The fish louse Argulus japonicus, a branchiuran crustacean of the Argulidae family, is attracting increasing attention because of its parasitic tendencies and significant health threats to the global fish farming. The mitogenomes can yield a foundation for studying the epidemiology, genetic diversity, and molecular ecology and therefore may be used to assist in the surveillance and control of A. japonicus. In this study, we sequenced and assembled the complete mitogenome of A. japonicus to shed light on its genetic and evolutionary blueprint. Our investigation indicated that the 15,045-bp circular genome of A. japonicus encodes 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), and two ribosomal RNAs (rRNAs) with significant AT and GC skews. Comparative genomics provided an evolutionary scenario for the genetic diversity of 13 PCGs: all were under purifying selection with cox1 and nad6 being the lowest and highest evolutionary rates, respectively. Genomewide phylogenetic trees established a close relationship between species of the families Argulidae (Arguloida) and Armilliferidae (Porocephalida) within Crustacea, and further A. japonicus and Argulus americanus were determined to be more closely related to each other than to others within the family Argulidae. Single PCG-based phylogenies supported nad1 and nad6 as the best genetic markers for evolutionary and phylogenetic studies for branchiuran crustaceans due to their similar phylogenetic topologies with that of the genome-based phylogenetic analyses. To sum up, these comprehensive mitogenomic data of A. japonicus and related species refined valuable marker resources and should contribute to molecular diagnostic methods, epidemiological investigations and ecological studies of the fish ectoparasites in Crustacea.